Strategy and human rights - Paquette, Laure (New York : Nova Science Publishers, Inc., 2019)
Raising the question -- Strategic analysis and development -- Strategic intervention : making the best of a bad idea -- An individual's fight for his own human rights : Edward Snowden -- A subnational group's strategy in dealing with a state : Committee of Concerned Scientists and the People's Republic of China -- A supra-national group's strategy in the supra-national system : Amnesty International and the defense of freedom of expression -- A state and a group of states : Poland and the UN system of human rights -- A group of states and a supranational group : Human Rights Watch and the UN -- A multiplayer, multilevel strategy in the supra national system : Amnesty International and women's rights -- A group of states and a group of states : the EU and the UN on human rights, 1995-2015.
Raising the question -- Strategic analysis and development -- Strategic intervention : making the best of a bad idea -- An individual's fight for his own human rights : Edward Snowden -- A subnational group's strategy in dealing with a state : Committee of Concerned Scientists and the People's Republic of China -- A supra-national group's strategy in the supra-national system : Amnesty International and the defense of freedom of expression -- A state and a group of states : Poland and the UN system of human rights -- A group of states and a supranational group : Human Rights Watch and the UN -- A multiplayer, multilevel strategy in the supra national system : Amnesty International and women's rights -- A group of states and a group of states : the EU and the UN on human rights, 1995-2015.
Includes bibliographical references and index.
Keywords: Human rights -- Case studies; International relations -- Planning; Political planning